Universal Values, Behavioral Ethics and Entrepreneurship - Clarke, Ruth (Journal of business ethics, 1997)
This is a comparison of graduate students attitudes in Spain and the United States on the issue of universal versus relativist ethics. The findings show agreement on fundamental universal values across cultures but differences in responses to behavioral ethics within the context of entrepreneurial dilemmas.